Qualitativeness of foreign language learning by students of non-professional specialties in the conditions of distance education. - Bukhinska, Tetiana; Hladkoskok, Lesia; Marchuk, Oksana (Актуальні питання гуманітарних наук: міжвузівський збірник наукових праць молодих вчених Дрогобицького державного педагогічного університету імені Івана Франка. Серія: «Педагогіка», 2022)
The article is devoted to the study of the quality of foreign language learning in the conditions of distance learning, as since March 2020 all universities have partially implemented distance and blended learning, and this has become a challenge not only for teachers but also for students. Emphasis is placed on the differentiation of the concepts of “distance education” and “distance learning”. The article identifies the need for a special approach of teachers to the choice of teaching aids in the process of learning a foreign language online, because the language, especially foreign, is, primarily, communication. The most effective means of information transmission in distance learning have been identified. Synchronous and asynchronous modes are distinguished through remote communication of participants in the educational process. The possibilities of using synchronous and asynchronous types of distance learning depending on the needs are briefly described. The survey, which was conducted among the students of all years of studying (excluding freshmen) at the Faculties of Economics and Law, revealed both the shortcomings and positive aspects of online learning. Students’ answers have been analyzed and the readiness of all participants in the educational process for digital learning has been established. The emergence of problems with education, which some students faced during the two years of the pandemic, has been substantiated. The constant continuous exchange of information between the student and the teacher has been confirmed. We have conducted a comparison of traditional and distance learning methods and the most effective means of assessment and monitoring foreign language skills from the point of view of students. The improvement of foreign language skills has been found in 73% of surveyed students, especially in the aspects of “speaking” and “grammar”. The opinion of students on the effectiveness of exams and tests in the online format has been clarified, and it has been suggested to compare the options for conducting the final control online and offline. The necessity of further research of the organization of distance learning of foreign languages in case of continuation of quarantine restrictions has been proven.
Keywords: distance learning, the study of foreign languages, online format, synchronous and asynchronous mode of learning, non-professional students.